Herbaceous Diversity in the Gumuk Ecosystem in Ledokombo District-Jember Regency with Varied Land Use Type - Maisyaroh, Wiwin; Hakim, Luchman; Sudarto, Sudarto; Batoro, Jati (Universitas Gadjah Mada, 2023)
Gumuk is a unique landscape in Jember Regency resulting from the eruption of Mount Raung that can provide ecosystem services through its ecological functions. Increased mining activity in Gumuk and land-use changes can lead to a decline in biodiversity and affect ecosystem services. This study aims to determine the diversity of herbaceous in the Gumuk ecosystem. Conducted in January - March 2021 in Ledokombo District, Jember Regency. The spatial distribution of Gumuk was carried out using GIS. Herbaceous sampling was carried out using 2x2 plots on three types of Gumuk utilisation, namely mixed gardens, sand mining, and stone mining. The results showed that there were 136 Gumuk in Ledokombo District. One hundred twenty herbaceous species (49 families) were found in all types of Gumuk. Mixed gardens have the highest species diversity (109 species, 49 families) compared to other types. Digitaria sanguinalis (L.) Scop. has high dominance in all types. Species dominance showed a moderate category for all types of Gumuk (D = 0.07). Community complexity in all types was in the high class (D' = 0.90) and species diversity was in the high class (H’ = 3.25). Evenness index € was different in the three types of Gumuk; in mixed gardens, the evenness of species was lower (0.23) than the other two types.